Evaluasi Heuristik E-Learning Institut Agama Hindu Negeri Tampung Penyang Palangka Raya - Purnawati, Ni Wayan; Alit Arsana, I Nyoman; Janardana Febrian Agus, I Putu (STMIK Palangkaraya, 2024)
Institute of Hindu Religion (IAHN) Tampung Penyang Palangka Raya has e-learning in an e-campus with complex features. Many e-learning features become ineffective, and make users unable to maximize their use. Therefore, a heuristic evaluation approach from Nielsen's is needed to find out the extent of usability in the e-learning. The heuristic evaluation method is a method used to find usability problems of a product using 10 heuristic evaluation principles. In this research, the assessment was carried out by 4 expert usability evaluators. The calculation of usability heuristic evaluation using severity ratings scale has been done. The results of the assessment based on heuristic evaluation on the IAHN-TP Palangka Raya e-campus application resulted in 24 problem findings. The highest value of the average severity rating (SR) is on the principle of error prevention and as much as 92% of the largest percentage is on the principle of visibility of system status. This research also provides recommendations for design improvements ranging from adding functions, changing appearance, and layout according to the results of the heuristic evaluation. These recommendations can be used as a consideration for the IAHN-TP campus management in improving the application.